Guanxi and high performance work systems in China: evidence from a state-owned enterprise. Issue 19 (28th October 2019) - Xian, Huiping; Atkinson, Carol; Meng-Lewis, Yue
Abstract: Existing high performance work system (HPWS) research has rarely considered cultural influences. This study investigates the relationships between guanxi, HPWS and employee attitudes in China. A data-set consisting of 226 employees in a Chinese state-owned enterprise in the railway sector was used to test the hypotheses. Using structural equation modelling as an analytical tool, we found that guanxi was positively related to HPWS and trust. Similar to research in the Western context, HPWS was found to be positively related to trust and job satisfaction. Moreover, the results also revealed that HPWS mediated between guanxi and both trust and job satisfaction. Theoretical and practical implications are both discussed.